Analisis Strategi Pengembangan Obyek Wisata Waduk Riam Kanan di Kabupaten Banjar - Subhan Abdilah; Noor Rahmini (PPJP Universitas Lambung Mangkurat, 2020)
This study aims to (1) determine the internal and external factors of right cascade reservoir tourism development in the Banjar district, and (2) develop the right cascade reservoir area in the Banjar district. There were six respondents in this study who were considered influential in determining village spending in Kayu Bawang Village, used in data processing using the SWOT method. The research results show that the development of the most appropriate strategy is the S-O strategy (1) Increase Tourist Perception to visit this tourism object because this tourism location is very strategic and has beautiful natural scenery and cold air. (2) Optimizing the role of the POKDARWIS (Tourism Awareness Group) of the Culture and Tourism Office of the Banjar District to promote these attractions.